Odpowiedzi

2010-02-24T16:19:19+01:00
A)-4c-46=-2
-4c=44/:(-4)
c=-11
b) 13+2x=3
2x=-10/:2
x=-5
c) -7=5x+1
-8=5x/:5
x=-1⅗
d)7x-21=5x
2x=21/:2
x=10,5
e)6y-13=-52
6y=-39/:6
y=-6,5
i)4x-4=3
4x=7/:4
x=1¾
j)3c+2=-70
3c=-68/:3
c=-22⅔
k)33-4x=4x
-8x=-33/:(-8)
x=4⅛
l)5-10x=-2x
-8x=-5/:(-8)
x=⅝
Najlepsza Odpowiedź!
2010-02-24T16:19:47+01:00
A)
-4c-46=-2
-4c=-2+46
-4c=44 /:(-4)
c= -11

b)
13+2x=3
2x=3-13
2x= -10 /:2
x= -5

c)
-7=5x+1
5x= -7-1
5x= -8 /:5
x=- 8/5
x= -1 i 3/5

d)
7x-21=5x
7x-5x=21
2x=21 /:2
x= 10 i 1/2

e)
6y-13=-52
6y= -52+13
6y= -39 /:6
y= -6 i 1/2

i)
4x-4=3
4x=3+4
4x=7 /:4
x=7/4
x=1 i 3/4

j)
3c+2=-70
3c= -70-2
3c= -72 /:3
c= -24

k)
33-4x=4x
-4x-4x=-33
-8x= -33 /: (-8)
x= 4 i 1/8

l)
5-10x=-2x
-10x+2x= -5
-8x=-5 /:(-8)
x= 5/8